Handbook of research on green engineering techniques for modern manufacturing - Uthayakumar, M., 1975-; Raj, S. Aravind; Ko, Tae Jo; Kumaran, S. Thirumalai; Davim, J. Paulo (Advances in mechatronics and mechanical engineering (AMME) book series., 2019)
"This book addresses the challenges in new manufacturing and industrial engineering techniques focuses towards green manufacturing, reduction of pollutants and implementation of sustainability concepts in current scenario. It explores different aspects of advanced manufacturing techniques, additive manufacturing, green manufacturing and lean manufacturing"--